The Epidemiology of Chronic Kidney Disease-Related Pruritus and its Effect with Sleep Quality in Hemodialysis Patients in Pakistan A Cross-Sectional Study - Mazhar Ul Haq, Rahmat Ali Khan, Najamuddin, Raza Muhammad Khan, Sultan Zafar, (Pakistan Journal of Medical & Health Sciences, 2022)
A glomerular filtration rate of less than 60 ml/min/1.73 m2 for more than three months is the medical definition of chronic kidney disease (CKD) caused by damaged kidneys. The incidence of chronic kidney disease, which can be fatal if left untreated, has been rising for the past 30 years. An unpleasant condition, Pruritus due to chronic renal disease causes itching and decreases the quality of sleep. This study aims to examine the factors associated with Pruritus in CKD patients on maintenance hemodialysis and their impact on sleep quality. Duration and Place: Since 01/01 2019 and ending in 30/06/2019 that year, I will be working as a Post graduate trainee Nephrology in the Nephrology Department at the Institute of Kidney Diseases in Peshawar. Methodology: The department of Nephrology Institute of kidney diseases provided 120 patients with the chronic renal illness. Patients with chronic kidney disease who experienced Pruritus and sleep disruption were included in the study, but those with rashes and Pruritus unrelated to CKD were not. All patients were questioned about their age, gender, typical sleeping habits, illness severity, poor sleep quality, and the location of any pruritus they experienced. Results: CKD-associated This is how pruritis was dispersed: Eighty-one Percent of patients were older than 90, while the remaining 24 percent were younger. Only 43% of those diagnosed with Pruritus reported it affecting their ability to sleep, while 57% reported no such disruptions; also, only 31% of those diagnosed were female, and 74% were male. About 56 percent of those suffering from Pruritus have it quite seriously, whereas 44 percent do not. 62% of Pruritus people experience it on their trunks, compared to 38% elsewhere. A high degree of Pruritus was associated with the female gender, affected body parts, and lack of sleep. Conclusion: Pruritus (sometimes called "uremic pruritus") is the most prevalent skin symptom among persons with ESRD. Despite the absence of evidence linking it to uremia, a significant connection exists in men over 45, causes sleep disruption, and predominates in the trunk. Keywords: CKD-Related Pruritus, Effect, Sleep Quality, Hemodialysis